O território quilombola de Araquembaua, Baião-Pa. - LOPES, Carla Joelma de Oliveira (Universidade Federal do Pará, 2018)
This paper presents a framework of relatively recent territorial transformations in the Amazon, a framework triggered by the Brazilian legal frameworks in the Federal Constitution of 1988 concerning the recognition, demarcation and titling of quilombola populations. In this sense, the quilombola territory of Araquembaua located in the municipality of Baião (PA) was taken as object of analysis. The general objective was to analyze the changes and permanences that were taking place within the territory, starting from the titling process that took place in the year 2002, focusing on three central elements: land, work and family. It was also sought to understand the territorialities developed by the subjects in the community before the titling, as well as to identify the territorial, technical and political factors that explain the titling of the quilombola territory in Araquembaua. Finally, we tried to analyze the territorialities that are expressed in the territory after the titration. It was hypothesized that the land uses in the community were not homogenous and signaled relations of conflict, resistance and antagonism in relation to the assumption of the ethnic identity of the Quilombola, which gave indications that the group's option materialized mainly a territorial strategy to guarantee The security of the use of the territory. The adopted theoretical framework highlights the categories used territory and territoriality. The results revealed that quilombola titling was an important event within the community, but it did not change the way of life of the population nor was it able to help overcome the poverty and inequalities historically imposed on the territory.